Fabrication and Characterization of Calcium Carbonate Microspheres - Nadiawati, Alias; Abd Manaf, Ali; Javeed Shaikh, Mohammed; Intan Nabila, Sabri (2013)
Calcium carbonate (CaCO3) microspheres (μ-spheres) are widely used inorganic templates (or cores) for fabricating nano-engineered microcapsules. In the current work, fabrication of CaCO3 μ-spheres was carried out using precipitation reaction between calcium chloride (CaCl2) and sodium carbonate (Na2CO3) solutions under vigorous stirring. Two different fabrication approaches were used, namely membrane filtration and centrifugation approaches, in order to prepare spherical CaCO3 μ-spheres with a narrow size distribution. Several different experimental factors can affect the size and shape of CaCO3 μ-spheres. For the membrane filtration approach, the experimental factors tested included mixing procedure of solutions, stirring speeds, drying techniques, and types of filter paper used. For the centrifugation approach, the experimental factors tested included mixing procedure of solutions, stirring speeds, centrifugation times, drying techniques, and quantity of washing agents used. The size measurements and shape of the CaCO3 μ-spheres were investigated using compound microscopy. Scanning electron microscopy (SEM) was used to reveal the fine surface morphological details of the CaCO3 μ-spheres. Overall results indicate that the centrifugation approach can yield better CaCO3 μ-spheres as compared to the membrane filtration approach in terms of narrow size distribution and spherical shape. The CaCO3 μ-spheres will be used as templates for fabricating nano-engineered dynamic microcapsules (DynaMicCaps) containing calmodulin (CaM) protein for drug delivery applications.